CONTRIBUTIONS TO A HISTORY OF MEXICAN DIPTEROLOGY . PA RT II.- THE BIOLOGIA CENTRALI-A MERICANA - Papavero, Nelson; Ibáñez Bernal, Sergio (Instituto de Ecología, A.C., 2003)
In this second contribution to the history of Mexican Dipterology, general remarks of the Biologia- Centrali A mericana, the authors, the collectors and their trips are presented. Dealing specifically with Diptera, some aspects of the life and works of the contributors to this work are included. Here are listed all the Mexican Diptera species-names proposed by Karl Robert Romanovitch Baron von den Osten Sacken (78 species), Samuel Wendell Williston (200 species), John Merton A ldrich (47 species), William Morton Wheeler and A xel Leonard Melander (18 species), and Frederik Maurits Van Der Wulp (610 species). Included are a total of 953 specific names of the following 41 current families (in phylogenetic order): Tipulidae: 16, Bibionidae: 2, Ditomyiidae: 1, Keroplatidae: 2, Mycetophilidae: 1, Culicidae: 1, Ceratopogonidae: 2, Tabanidae: 12, Pantophtalmidae: 1, Rhagionidae: 7, Stratiomyidae: 26, Therevidae: 1, Mydidae: 3, A pioceridae: 1, A silidae: 59, A croceridae: 3, Nemestrinidae: 1, Bombyliidae: 72, Empididae: 20, Dolichopodidae: 48, Platypezidae: 1, Syrphidae: 54, Pipunculidae: 5, Conopidae: 6, Micropezidae: 12, Tanypezidae: 1, Psilidae: 2, Otitidae: 12, Platystomatidae: 8, Tephritidae: 39, Richardiidae: 5, Sciomyzidae: 10, Lauxaniidae: 1, Heleomyzidae: 3, Scatophagidae: 4, A nthomyiidae: 11, Muscidae: 40, Calliphoridae: 1, Sarcophagidae: 44, Tachinidae: 412, Hippoboscidae: 3. The original reference, type-locality, depository museum or collection, current taxonomic status of each species- names and additional references are given.